Modification of the Mechanical Properties of Ti-Al-V Alloys with Variation of Aluminum: Modification of the Mechanical Properties of Ti-Al-V Alloys - Amir, Aqsa; Atiq, Shabbar; Ibrahim, Athar; Qamar, Afeera; Habiba, Ume; Khalil, Natasha (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
In this study, the development of ternary alloys of titanium, Ti91Al5V4, Ti90.5Al5.5V4 and Ti89.5Al6.5V4 by Vacuum Arc melting technique was carried out. It was followed by Homogenization in three zone furnace for 16 hours and solution treatment at 1000°C followed by water cooling. Aging treatment at 500°C followed by furnace cooling was carried out and effects of aluminum contents on mechanical properties of Ti-Al-V system were studied. The solution treatments at temperature 1000°C followed by water cooling led to the formation of α′ martensite. Microstructures analyzed in the results confirmed the presence of major alpha Ti and very minute beta-Ti phase. X-Ray Diffraction confirmed the HCP( hexagonal close packed) structure for alpha-Ti phase as the highest peak and BCC (body centered cubic) structure for β titanium as very minor peak. An increasing trend of all mechanical properties (yield strength, tensile strength, toughness, ductility) was found with increase in aluminum content.